First ectomycorrhizal syntheses between Astraeus sirindhorniae and Dipterocarpus alatus (Dipterocarpaceae), pure culture characteristics, and molecular detection - NUTTIKA SUWANNASAI; PREEYAPORN DOKMAI; AKIYOSHI YAMADA; ROY WATLING; CHERDCHAI PHOSRI (Society for Indonesian Biodiversity, 2020)
Abstract. Suwannasai N, Dokmai P, Yamada A, Watling R, Phosri C. 2020. First ectomycorrhizal syntheses between Astraeus sirindhorniae and Dipterocarpus alatus (Dipterocarpaceae), pure culture characteristics, and molecular detection. Biodiversitas 21: 231-238. This study provides the first mycorrhization of Astraeus sirindhorniae and its cultural characteristics on nutrient media. An attempt has been made to introduce spore suspension and mycelial inocula of A. sirindhorniae onto seedlings of Dipterocarpus alatus. After 6 months seedlings were harvested, measured for growth and morphological descriptions of the ectomycorrhizas formed with D. alatus seedlings were made. The fungus has increased the growth of D. alatus seedlings. Further, it can be confirmed that the primers designed (GAPK126F/GAPK379R) have been successful when applied for the detection of ectomycorrhizal formation of A. sirindhorniae in vivo.